Cases on lean thinking applications in unconventional systems - Satolo, Eduardo Guilherme [UNESP]; Calado, Robisom Damasceno (IGI Global, 2022)
Lean thinking involves more than just eliminating waste; through its five guiding principles-value, value chain, continuous flow, pull production, and perfection-its successful applications are commonly found in the manufacturing sector. Although its application and benefits to companies is no longer contested, it is rare to find works that consolidate applications of lean thinking in sectors that are unconventional, such as healthcare and government.